Analisis empiris faktor faktor yang mempengaruhi kebijakan dividen - NICKEN DESTRIANA (Jurnal Bisnis dan Akuntansi, 2016)
The purpose of this research is to analyze the effect of return on equity, operating cash flow, total assets turnover, company size, debt to total assets, collateralizable assets, company life cycle, and asset growth to dividend policy. Population in this research is nonfinancial companies which listed on the Indonesian Stock Exchange with period 2011 until 2013. The sample selected by using purposive sampling method, which consist 68 nonfinancial companies meet the sampling criteria. Multiple regression is used as the data analysis method. The result shows operating cash flow and asset growth have influence on companies’ dividend policy. However, return on equity, company size, debt to total assets, company life cycle, total assets turnover and collateralizable assets have no influence on companies’ dividend policy.